Bimanual non-congruent actions in motor neglect syndrome: a combined behavioral/fMRI study - Garbarini, F.; Turella, L.; Rabuffetti, M.; Cantagallo, A.; Piedimonte, A.; Fainardi, E.; Berti, A.; Fadiga, L. (Frontiers in Human Neuroscience, 2015)
In Motor Neglect (MN) syndrome, a specific impairment in non-congruent bimanual movements has been described. In the present case-control study, we investigated the neuro-functional correlates of this behavioral deficit. Two right-brain-damaged patients, one with (MN+) and one without (MN-) MN, were evaluated by means of functional Magnetic Resonance Imaging (fMRI) in a bimanual Circles-Lines paradigm. Patients were requested to perform right-hand movements (lines-drawing) and, simultaneously, congruent (lines-drawing) or non-congruent (circles-drawing) left-hand movements. In the behavioral task, MN- patient showed a bimanual-coupling-effect, while MN+ patient did not. The fMRI study showed that in MN-, a fronto-parietal network, mainly involving the pre-supplementary motor area (pre-SMA) and the posterior parietal cortex (PPC), was significantly more active in non-congruent than in congruent conditions, as previously shown in healthy subjects. On the contrary, MN+ patient showed an opposite pattern of activation both in pre-SMA and in PPC. Within this fronto-parietal network, the pre-SMA is supposed to exert an inhibitory influence on the default coupling of homologous muscles, thus allowing the execution of non-congruent movements. In MN syndrome, the described abnormal pre-SMA activity supports the hypothesis that a failure to inhibit ipsilesional motor programs might determine a specific impairment of non-congruent movements.